If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -45 = 11 Reorder the terms: -45 + Y = 11 Solving -45 + Y = 11 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + Y = 11 + 45 Combine like terms: -45 + 45 = 0 0 + Y = 11 + 45 Y = 11 + 45 Combine like terms: 11 + 45 = 56 Y = 56 Simplifying Y = 56
| -2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3 | | y=-4x-31 | | a=5-9a+8 | | 6x+8y-2x-y= | | 3/4=87*9 | | 7x-12-2x=7x-9 | | (x-1)+(2x+3)+(2x+3)=180 | | 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 | | y-5=-1/8x | | 7x+3y=5 | | 196*47/49*1/16 | | p-r=c | | 20+15x/2=21 | | 2(5-n)=-25 | | 5/7x=30 | | x+2x+2=10 | | 5/2+5/2y=2y-4 | | 6-2(3x-5)=-8 | | 14+8x=55 | | w=-r | | 12x-170=4x-10 | | 11x-2(x-7)=9(x+1)+7 | | a^2-13a+22=0 | | 7t=4*49 |